Entrepreneurship, innovation and technology a guide to core models and tools - Lorenzo, Oswaldo; Kawalek, Peter; Wharton, Leigh
"The combination of entrepreneurship, innovation and technology has become the source of disruptive business models that transform industries and markets. The integrative understanding of these three drivers of today's economy is fundamental to business. Entrepreneurship, Innovation and Technology aims to connect core models and tools that are already created by well-known authors and scholars in order to deliver a unique guide for building successful business models through the adoption of new technologies and the use of effective innovation methods. The book goes through the entrepreneurial lifecycle, describing and applying core innovation models and tools such as the business model canvas, lean startup, design thinking, customer development and open innovation, taking into consideration disruptive technologies such as mobile internet, cloud computing, internet of things and blockchain. Finally the book describes and analyses how successful cases have been applying those models and technologies. With the mix of an academic and practitioner team, this book aims to go against the grain by its positioning of entrepreneurship in the modern technology economy. This book will prove to be a vital text for any student, specialist or practitioner looking to succeed in the field"